Adult Inflammatory Bowel Disease, Physical Rehabilitation, and Structured Exercise. Issue 12 (29th May 2018) - Elia, Jessica; Kane, Sunanda
Abstract: Primary symptoms of inflammatory bowel diseases (IBDs) are well characterized, but secondary complications including fatigue, pelvic dysfunction, sarcopenia, osteopenia, and overall physical decompensation are less well studied. Symptoms and complications interfere with medical outcomes, physical function, working capacity, and overall quality of life. Although several systematic review articles address the role of exercise, to date none have explored the role of physical rehabilitation programs. The aims of this article are to review the existing IBD and physical rehabilitation literature and identify gaps in knowledge and opportunities for future research with the intent to then develop a guideline for clinical use. :